THE MYTH OF HIGH PERFORMANCE ORGANIZATION (HPO): THE TOP PRIORITIES FOR BUILDING A MORE COMPETITIVE COMPANY - Varga, János; Csiszárik- Kocsir, Agnes (PEOPLE: International Journal of Social Sciences, 2019)
In his book “Leading at a higher level” Ken Blanchard goes to great lengths to examine and to show the most relevant conditions of the highest performing companies. Another author, Jim Collins, also underlines that there are enterprises that are able to achieve strong results in the longer term too, but these companies implemented not just any business model. HPO – or high-performance organization – can also be interpreted as a special business model.. The purpose of the study is to summarize the characteristics of the high-performance organizations and the SCORES model, and additionally to examine how typical the excellence culture is of the domestic small and medium-sized enterprises. Following the presentation of the conceptual background, we will introduce the relevant results of a questionnaire survey conducted in Hungary, and we will make an effort to identify the companies that truly have the features of the high-performance organizations (HPO).